Interpersonal Family Dynamics Relate to Hippocampal CA Subfield Structure - Coughlin, Christine; Ben-Asher, Eliya; Roome, Hannah E.; Varga, Nicole L.; Moreau, Michelle M.; Schneider, Lauren L.; Preston, Alison R. (Frontiers in Neuroscience, 2022)
Social environments that are extremely enriched or adverse can influence hippocampal volume. Though most individuals experience social environments that fall somewhere in between these extremes, substantially less is known about the influence of normative variation in social environments on hippocampal structure. Here, we examined whether hippocampal volume tracks normative variation in interpersonal family dynamics in 7- to 12-year-olds and adults recruited from the general population. We focused on interpersonal family dynamics as a prominent feature of one’s social world. Given evidence that CA1 and CA2 play a key role in tracking social information, we related individual hippocampal subfield volumes to interpersonal family dynamics. More positive perceptions of interpersonal family dynamics were associated with greater CA1 and CA2/3 volume regardless of age and controlling for socioeconomic status. These data suggest that CA subfields are sensitive to normative variation in social environments and identify interpersonal family dynamics as a impactful environmental feature.